Analysis of The Three Main Categories of Defense Industrial Policy In Law No. 16 Of 2012 - Iqomudin Akhyar, Wira; G. Royke Deksino; Jupriyanto Jupriyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The main problems in defense industrial policy relate to issues of strength, prestige and prosperity. The defense industry policy instrument in Law No. 16 of 2012 projects policy direction in three main aspects. This article aims to analyze the three main categories of the defense industry in the form of procurement, research and development as well as export regulations for defense industry products in Law No. 16 of 2012. The research method uses qualitative methods. The analysis orientation uses a conceptual approach and legal regulations. The results found explain that the policy direction in the three main categories of the defense industry is in line with import substitution and export promotion policies. Fulfillment of defense industry legal instruments is based on fifteen principles that bind the policy. Defense industrial policy options are commonly used in developing the defense industry of developed countries in the world. The main principle of policy objectives leads to technological innovation schemes for security and defense equipment. The implications of the chosen policy can move the value chain of defense industry products and open up new job opportunities.